Inclusive Leadership and Career Sustainability: Mediating Roles of Supervisor Developmental Feedback and Thriving at Work - Fang, Yang-Chun; Ren, Yan-Hong; Chen, Jia-Yan; Chin, Tachia; Yuan, Qing; Lin, Chien-Liang (Frontiers in Psychology, 2021)
Career sustainability is a hot issue in the academic and practical circles. Technology advancements and COVID-19 have jeopardized career sustainability. Numerous studies have explored the influence of individual characteristics on career sustainability, but few have focused on leadership. In addition, cultural factors must be considered because leadership is rooted in culture. In particular, inclusive leadership reflects traditional Chinese culture. Therefore, based on self-determination and social exchange theories, we analyzed the effects of inclusive leadership on career sustainability as well as the roles of thriving at work and supervisor developmental feedback (SDF) in career sustainability. In total, 363 samples were collected from China. The results revealed that inclusive leadership improves career sustainability through SDF and thriving at work. Theoretically, our study fills the research gap and establishes a mechanism and theoretical framework for inclusive leadership and career sustainability. Practically, we offer guidance for enterprises to cultivate inclusive leadership and improve career sustainability.